Graduate employability: perception of graduate students on soft skills towards employability in Bangladesh - Sarker, Md Atiqur Rahman; Hashim, Junaidah; Haque, A. K. M. Ahasanul; Juhdi, Nurita (Research Publishing Academy (RPA), 2021)
Career opportunity for newly graduated candidates in Bangladesh is challenging at present due to high job demand, skill gap and lack of practical experiences. Thus, this study emphasises on student’s perception regarding the importance of soft skills acquisition towards their employability. This study has collected survey responses from 326 final year students from ten different private and public universities in Bangladesh. Structural Equational Modelling (SEM) technique has been used to investigate the relationship between different soft skills and employability through analysis of Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Significant relationships among communication, critical thinking, teamwork and employability have been found in this study. This study is limited to the soft skills acquisition and graduates’ employability. Further study can be conducted between the relationship of different soft skills and Human Resource Management (HRM) practices. This study provides a significant contribution to the literature by exploring the key soft skills that have relationship with employability. It also promotes the acquisition and practice of soft skills in finding jobs for newly graduated job candidates